An audit of acute kidney injury : a prospective study of the epidemiology, management and outcome of patients with acute kidney injury, over a 12 month period at Groote Schuur Hospital, Cape Town, South Africa - Dlamini, Thandiwe Angela Lerato (Department of Medicine, 2015)
Includes bibliographical references.